Factors Associated with Treatment Adherence among Tuberculosis Patients in Gandaki Province of Nepal (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2020)
Introduction: Poor adherence to the treatment regimen is a major cause of treatment failure and the emergence of drug resistance among TB patients. The emergence of resistance to anti-tuberculosis drugs and particularly of multi-drug resistance (MDR), Pre-extensively drug resistance tuberculosis (Pre-XDR) and extensively drug resistance (XDR) tuberculosis have become a major public health problem in several countries and an obstacle to effective global TB control.Methodology: This research was health facility based cross-sectional study and carried out among TB patients registered under DOTS and receiving treatment more than or equal to 60 days from health facilities of Gandaki province of Nepal. Structured interview schedule and validated questionnaires were used for data collection. Treatment Adherence was assessed by using Nepali version of Morisky treatment adherence scale (MMSA-8) questionnaires. Data were entered in Epi-data software and analysis was performed with the help of the Statistical Package for Social Science (SPSS). The odds ratio with a 95%CI was calculated and a P-value of